The Effect of Non-Performing Loan Level, Credit Distribution, and Operating Expenses on the Return on Equity in Banking Sub-Sector Companies in KBMI Category 3 Listed on the Indonesia Stock Exchange for The Period 2020-2024 - PASUPATI, Bayu; SETENA, Made (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the effect of non-performing loans, credit distribution rates, and operational expenses on the return on equity of KBMI 3 category banking sub-sector companies listed on the Indonesia Stock Exchange (IDX). The approach used is quantitative with an explanatory research type. The sample was determined using purposive sampling and consisted of 9 companies. Secondary data were obtained from the 2020-2024 financial reports through the IDX official website and analyzed using multiple linear regression with SPSS version 25. The results show that partially, non-performing loans (NPL) do not have a significant effect on return on equity (ROE), while loan-to-deposit ratio (LDR) and operating expenses (BOPO) have a significant effect. These findings contribute to the development of literature and provide practical benefits for management, investors, and regulators. This study has limitations in the number of variables studied and the scope of the sector is still narrow, so the results cannot be generalized widely.